Octa‐nonagenarians can perform video capsule endoscopy safely and with a higher diagnostic yield than 65–79‐year‐old patients. Issue 10 (5th July 2022) - Thurm, Tamar; Gluck, Nathan; Barak, Orly; Deutsch, Liat
Abstract: Background: Video capsule endoscopy (VCE) is an effective, noninvasive modality for small bowel (SB) investigation. Its usage in the older adults is rising. However, data in octa‐nonagenarians regarding diagnostic yield and motility are lacking. Our aim was to evaluate and compare safety and efficacy of VCE between age subgroups of older adult patients. Methods: This was a retrospective study of prospectively documented data. All consecutive VCEs of patients ≥65 years (01/2010–12/2017) were included. Patients unable to swallow the capsule or videos with significant recording technical malfunction were excluded. The cohort was divided into the younger group aged 65–79 years old and octa‐nonagenarians aged ≥80 years old. Indications for referral, diagnostic yield and transit times were compared between groups. Results: A total of 535 VCEs were performed in 499 older adult patients (51.2% males); 82.8% were 65–79 years old and 17.2% were ≥80 years old. The ≥80‐year‐old group had higher rates of clinically significant findings (52.7% vs. 40.0%, p  = 0.025), active bleeding (12.5% vs. 6.5%, p  = 0.053) and angioectasia (36.0% vs. 23.4%, p  = 0.014). Crohn's disease was newly diagnosed in approximately 8% of the entire cohort and 12% of the ≥80 years old. Anemia was the most common indication in both groups, followed by overt bleeding in the ≥80‐year‐old group (25% vs. 9.9% in 65–79‐year‐old group, p  < 0.001) and Crohn's disease in the 65–79 years old (17.2% vs. 5.4% in ≥80 years old, p  = 0.004). Groups were comparable in transit time and cecal documentation rates. Conclusions: In octa‐nonagenarians, VCE is as safe as in younger older‐adults with a higher diagnostic yield of significant and treatable conditions.